2013
DOI: 10.5005/jp-journals-10024-1375
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Microleakage of Class V Composite Restorations with Fiber Inserts

Abstract: Aim: This study investigated the effect of different fiber inserts (glass and polyethylene), bonding agents, and resin composites on the gingival margin microleakage of class V composite restorations. Materials and methods:Sixty premolars were sterilized and mounted in acrylic resin bases. Class V cavities were prepared buccally and lingually, 1 mm below the cementoenamel junction, comprising 12 groups (n = 10). In the experimental groups fiber inserts were cut and placed at the gingival seat, while the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Fifteen full-text articles were evaluated, and two articles were excluded due to using the tested material as an endocrown or extended it to the roots. Two more articles were found by manual search and cross references [26,27] producing a number of 15 full-text comparative articles, that entirely met the inclusion criteria [4,[8][9][10][11][26][27][28][29][30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen full-text articles were evaluated, and two articles were excluded due to using the tested material as an endocrown or extended it to the roots. Two more articles were found by manual search and cross references [26,27] producing a number of 15 full-text comparative articles, that entirely met the inclusion criteria [4,[8][9][10][11][26][27][28][29][30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with the findings reported by Ahmed et al, who found that the type of the composite material used (Filtek ® Z250 vs Filtek LS (3M ESPE)) had no significant effect on gingival microleakage, rather the bonding agent type was more critical and had a significant effect. 12 Furthermore, Rengo et al found no significant differences in the microleakage of class II cavities restored with bulkfill composites (G-aenial ® Universal Flo bulk-fill, G-aenial Flo bulk-fill and Kalore ® bulk-fill (GC Corporation, Tokyo, Japan)) in comparison to that of the cavities incrementally restored with conventional composites (G-aenial Universal Flo, G-aenial Flo and Kalore (GC Corporation)), using the same adhesive system (G-aenial Bond (GC Corporation)) with all the groups. 26 The statistical analysis did not reveal significant differences in the mean microleakage scores, when the values obtained for each group after 6 months were compared with the values obtained after 24 h, in spite of an obvious increase in the mean score.…”
Section: Discussionmentioning
confidence: 99%
“…1,12 The half with the deepest dye penetration was used to represent the tooth. 1,12 The extent of dye penetration was determined by an examination with a stereomicroscope (Wild M3Z Stereo Microscope; Leica Microsystems (Schweitz) AG, Heerbrugg, Switzerland) at a magnification ×10, according to a 5-point scale: -0: no dye penetration; -1: dye penetration limited to the outer half of the gingival floor; -2: dye penetration extended along the entire gingival floor (i.e., beyond the outer half of the gingival floor); -3: dye penetration extended along the gingival wall and up to half of the axial wall; -4: dye penetration extended along the gingival floor and the entire axial wall. In addition, a digital camera (Canon PowerShot S 120; Canon, Inc., Tokyo, Japan) was used to capture photographic images for each selected section (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…After marginal gaps were measured, all the restored teeth (n=80) prepared for the microleakage test, then the root apices of the teeth were sealed with sticky wax. The whole surface of each tooth was coated with two layers of a nail polish 1mm away from the restoration margins could eliminate microleakage from areas other than the restoration margins that could lead to false positive results (11). The teeth were immersed in 0.5% basic fuchsine dye solution for 24 hours at room temperature.…”
Section: Microleakage Testingmentioning
confidence: 99%